Preventive Care and Evaluation of the Adolescent with a Breast Mass - Jayasinghe, Yasmin (Seminars in Plastic Surgery, 2013)
Adolescents have little knowledge of preventive breast care or breast screening, yet exposures in youth influence the risk of future breast disease.Nipple piercing increases the risk of trauma and breast infection. Alcohol consumption, smoking, nutrition, obesity, reproductive factors, previous cancer and chest radiotherapy, family history of breast cancer or genetic mutation increase the risk of breast cancer. Breast cancer is rare in adolescents and currently genetic testing is not recommended in those under 18 years, as medical surveillance is not usually recommended until around 25 years. Screening measures include clinical breast exam every 1 to 3 years, and breast self-awareness in healthy women from 20 years; and at least annual breast self examination, with annual clinical breast examination, mammography and magnetic resonance imaging in high-risk patients from 25 years. Breast ultrasound is used in diagnostic evaluation of breast masses in adolescents as mammography is less sensitive in young women.
Keywords: adolescent; breast cancer; breast screening; BRCA1/2; body piercing